Reduction of maternal mortality due to preeclampsia in Colombia-an interrupted time-series analysis (Colombia Medica, 2014)
Introduction.  Preeclampsia is the most important cause of maternal mortality in developing countries. A comprehensive prenatal care program including bio-psychosocial components was developed and introduced at a national level in Colombia. We report on the trends in maternal mortality rates and their related causes before and after implementation of this program. Methods: General and specific maternal mortality rates were monitored for nine years (1998-2006). An interrupted time-series analysis was performed with monthly data on cases of maternal mortality that compared trends and changes in national mortality rates and the impact of these changes attributable to the introduction of a bio-psychosocial model. Multivariate analyses were performed to evaluate correlations between the interventions. Results: Five years after (2002–2006) its introduction the general maternal mortality rate was significantly reduced to 23% (OR= 0.77, CI 95% 0.71-0.82).The implementation of BPSM also reduced the incidence of preeclampsia in 22%  (OR= 0.78, CI 95% 0.67-0.88), as also the labor complications by hemorrhage in 25%  (OR= 0.75, CI 95% 0.59-0.90) associated with the implementation of red code. The other causes of maternal mortality did not reveal significant changes. Biomedical, nutritional, psychosocial assessments, and other individual interventions in prenatal care were not correlated to maternal mortality (p= 0.112); however, together as a model we observed a significant association (p= 0.042). Conclusions: General maternal mortality was reduced after the implementation of a comprehensive national prenatal care program. Is important the evaluation of this program in others populations.